Planejamento colaborativo no ensino de matemática a partir do desenho universal para a aprendizagem - Silva, Fabricio de Lima Bezerra (2021)
Universal Design for Learning has enabled strategies for the teaching and learning process of all students, considering the challenge for an inclusive education. Thus, this research has as general objective to analyze the process of collaborative construction of mathematics lesson plans based on the principles of Universal Design for Learning. The specific objectives are: a) to understand how teachers analyze their pedagogical practice for the inclusion of students with disabilities; b) verify the contribution, in the teachers' perception, on the use of the principles of Universal Design for Learning in the teaching of Mathematics; c) analyze the path of collaborative training for the development of lesson plans in Mathematics characterized by the use of the concept principles of Universal Design for Learning. The collaborating participants in the research were two mathematics teachers in the final years from Elementary School and a teacher from the Specialized Educational Service who worked in the school's multifunctional resource room. The research has a theoretical dialogue based on the principles and guidelines of Universal Design for Learning about the construction of lesson plans developed with teachers in the type of collaborative research with a qualitative approach. For the development of the research, nine meetings were held with the three teachers on a virtual platform, in which the following topics were addressed: presentation of the proposal and conducting interviews; discussion of collaborative work and the concept of Universal Design for Learning; analysis of the principles of Universal Design for Learning (three meetings); instructions for collaborative building lesson plans from the perspective of Universal Design for Learning; production of plans (two meetings); and, finally, the evaluation of the work done. Referring to data collection, a script was previously prepared for conducting semi-structured interviews with collaborating teachers and video recordings of the meetings with these professionals were made. For analysis, after transcribing the data, the thematic proposal was used. As a result, the collaborating teachers considered that Universal Design for Learning is an important concept in the search for the perspective of participation of all students in pedagogical activities. The lesson plans scripts developed, based on the collaborative training model, enabled professionals to have different aspects of teaching at their disposal. However, the lesson plans scripts developed by the teachers proved to be limited about offering multiple strategies. It was concluded, therefore, that the collaborative planning between the researcher, the teachers of common education and the teacher of Specialized Educational Service demonstrated to have potential to reach effective and inclusive practices.